Strategic Planning for the Development of Educational Ecotourism in Educational Institutions in Batu City - Refiana Dwi Maghfiroh; Irma Kurniasari (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
The city of Batu is known as one of the main tourist destinations in East Java with abundant natural potential, ranging from agriculture and plantations to beautiful mountain ecosystems that can be developed into ecotourism that emphasizes a balance between economic activities, environmental preservation, and community empowerment. Educational institutions can play a strategic role in the development of ecotourism, both as centers of learning, drivers of entrepreneurship, and facilitators of community empowerment. Through the establishment and development of ecotourism business units, educational institutions can create practice-based learning experiences, while also building the economic independence of the institution. This training aims to provide comprehensive understanding to tourism stakeholders, particularly ecotourism managers, in supporting the sustainability of ecotourism businesses.